Facilitating student well-being: relationships do matter. Issue 4 (1st October 2016) - Graham, Anne; Powell, Mary Ann; Truscott, Julia
Abstract: Background: Alongside academic and vocational goals, schools are increasingly being called upon to address student well-being. Existing evidence suggests that strong relationships and a sense of connectedness in school communities are important for fostering subjective well-being. However, identifying the specific nature of such relational dynamics, and accommodating the 'personal' within school cultures increasingly dominated by 'performance' narratives, remains a problematic task. Purpose: This paper draws on Honneth's recognition theory to offer fresh insight into how relationships act to facilitate and limit the experience of well-being at school. We suggest that such an approach holds considerable potential for developing teachers' understanding of the tacit and explicit ways they and their students experience being cared for, respected and valued and the ways in which such actions impact on well-being. Design and methods: The paper reports the qualitative findings from a large mixed-method study, involving students and staff across primary and secondary schools in three regions of Australia. The qualitative phase involved focus groups with 606 primary and secondary students and individual interviews with 89 teachers and principals. Results: Across the focus groups and interviews, students and teachers placed substantial emphasis on the importance of relationships, while reporting differences in their views about which relationships support well-being. Alongside this, there were differences in the importance teachers and students placed on each of the three strands of Honneth's recognition theory (translated for this study as being cared for, respected and valued) for influencing student well-being. Conclusions: The findings affirm the critical role that relationships play in promoting well-being in the context of schools. Using recognition theory to analyse students' and teachers' views and experiences of well-being provides much greater insight into how these relationships are enacted – this being through the mutual experience of being cared for, respected and valued – within the context of schools.